EFEITO DA FORMA FÍSICA E DO VALOR DE ENERGIA METABOLIZÁVEL DA DIETA SOBRE O DESEMPENHO DE FRANGOS DE CORTE - FLEMMING, J. S.; MONTANHINI NETO, R.; ARRUDA, J. S.; FRANCO, S. G. (Archives of Veterinary Science, 2002)
O presente trabalho buscou avaliar o desempenho zootécnico de frangos de corte da linhagem ROSS, do 1o ao 49o dia de idade, submetidos a rações com diferentes densidades energéticas e formas físicas (farelada e peletizada). O experimento foi conduzido nos meses de Agosto e Setembro de 1999, no aviário experimental da Cooperativa Agrícola Consolata Ltda., em Cafelândia (PR). Num delineamento em blocos casualizados, foram testados os tratamentos: T1 ração farelada, com energia metabolizável média de 3137,5 kcal/kg; T2 ração farelada, com 3100 kcal/kg; T3 ração peletizada, com 3100 kcal/kg e; T4 ração peletizada, com 3062,5 kcal/kg. Não foram observadas diferenças significativas (P > 0,05) ao variar-se o nível energético das dietas. Rações peletizadas proporcionaram às aves: maior conversão alimentar e mortalidade no período total (1 a 49 dias de idade) (P<0,05); menor ganho de peso e maior conversão alimentar na fase final (43 a 49 dias de idade) (P < 0,05) e maiores ganho de peso e consumo de ração na fase inicial (15 a 28 dias de idade) (P < 0,05). Effect of dietary ration type and metabolizable energy value on performance of broilers Abstract The main aim of the present research work was to carry a zootechnic evaluation of broilers of the Ross lineage from the 1st up to the 49th day of age. in regard to the different types of ration - branny and pelleted - and different energy densities. The experiment was carried out during August and September 1999 at the Cooperativa Agrícola Consolata Ltda (Cafelândia, PR - experimental aviary. The experiment was delineated in casually blocks with the following treatments: T1 - branny ration an average of metabolizable energy of 3137.5 kcal/kg; T2 - branny ration with 3100 kcal/kg; T3 -pelleted ration with 3100 kcal/kg; and T4 - pelleted ratio with 3062.5 kcal/kg. No significant differences were observed (P > 0.05) in regard to the variation of the diets energy levels. Pelleted rations, on the other hand, provided to the birds greater alimentary conversion as well as mortality during the whole period of 1 up to 49 days of age (P < 0.05); smaller weight earning and larger alimentary conversion in the final phase (43 to 49 days of age (P < 0.05) and larger weight earning and larger feed intake at the initial phase (15 to 28 days of age) (P < 0.05).